Effect of micro‐RNA on tenocytes and tendon‐related gene expression: A systematic review. Issue 11 (13th July 2018) - Dubin, Jeremy A.; Greenberg, Daniel R.; Iglinski‐Benjamin, Kag C.; Abrams, Geoffrey D.
ABSTRACT: The purpose of the review was to synthesize the current literature regarding the effect of miRNA on biological processes known to be involved in tendon and tenocyte development and homeostasis. Using multiple databases, a systematic review was performed with a customized search term crafted to identify any study examining micro‐RNA in relation to tendon and/or tenocytes. Results were classified based on the following categories: Gene expression, tenocyte development and differentiation, tendon tissue repair, and tenocyte senescence. A total of 3, 112 potentially relevant studies were reviewed, and after exclusion criteria was applied, 15 investigations were included in the final analysis. There were 14 specific miRNA included in this review, with 11 studies reporting on tendon‐related gene expression, five reporting on tendon development and/or tenocyte differentiation, six reporting on tendon tissue repair, and five reporting on tenocyte senescence. The miR‐29 family was the most commonly reported micro‐RNA in the investigation. We also report on a number of micro‐RNA which are associated with both positive and negative effects on tendon homeostasis. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2823–2829, 2018.